Behavioral cross-sensitization between testosterone and fenproporex in adolescent and adult rats - Conceição, C. Q. [UNESP]; Engi, S. A. [UNESP]; Cruz, F. C. [UNESP]; Planeta, C. S. [UNESP] (FapUNIFESP (SciELO), 2018)
The abuse of psychoactive drugs is considered a global health problem. During the last years, a relevant number of studies have investigated the relationship between anabolic-androgenic steroids (AAS) and other psychoactive drugs. AAS, such as testosterone, can cause a dependence syndrome that shares many features with the classical dependence to psychoactive substances. Pre-clinical evidence shows that there are interactions between testosterone and psychoactive drugs, such as cocaine. However, few studies have been performed to investigate the effect of repeated testosterone treatment on behavioral effects of amphetamine derivatives, such as fenproporex. The purpose of the present study was to investigate the effects of repeated testosterone administration on fenproporex-induced locomotor activity in adolescent and adult rats. Adolescent male Wistar rats were injected with testosterone (10 mg/kg sc for 10 days). After 3 days, animals received an acute injection of fenproporex (3.0 mg/kg ip) and the locomotor activity was recorded during 40 min. Thirty days later, the same animals received the same treatment with testosterone followed by a fenproporex challenge injection as described above. Our results demonstrated that repeated testosterone induced behavioral sensitization to fenproporex in adolescent but not in adult rats. These findings suggest that repeated AAS treatment might increase the dependence vulnerability to amphetamine and its derivatives in adolescent rats.
Keywords: Behavioral sensitization; Fenproporex; Rats; Testosterone